﻿La théorie des ruines d’Albert Speer ou l’architecture « futuriste » selon Hitler - Lamoureux, Johanne (RACAR : Revue d'art canadienne / Canadian Art Review, 1991)
This article reflects upon a few pages of Albert Speer’s memoirs on the Third Reich, in which the man who was Hitler’s first architect from 1934 to 1942, after a twenty-year term of imprisonment, offers his theory on the value of ruins. The architect himself considered this an active factor in establishing his privileged relation to the Führer, a theory that conceived the Reich’s official buildings in view of the beautiful ruins they would produce after centuries of neglect. This projective (instead of retrospective) treatment of the ruins, of which the modern period offers many an example, becomes a pressing issue with such a cumbersome and fundamentally anti-modern heritage as Third Reich constructions.Speer’s anticipation of the Antique-cum-Romantic inspired ruins was to impose stylistic, economic and pragmatic constraints on his projects for which the functional necessities of the present became less important than the programmed revelation of Nazi imperial glory. The counterpart (both real and symbolic) of ruins was to be found in the architectural debris of modern European cities produced under the competent care of Hitler’s first architect made armaments minister in 1942: Albert Speer.